Public opinion on smoke-free policies in restaurants and predicted effect on patronage in Hong Kong - Lam, T (BMJ Group, 2002)
Background: The Hong Kong government has proposed legislation for smoke-free policies in all restaurants and bars. This is opposed by certain sections of the catering industry. Objective: To assess public opinion on smoke-free restaurants and to estimate changes in patronage. Design: A population based, cross sectional random digit dialling telephone survey conducted from November 1999 to January 2000. Setting and participants: 1077 randomly selected subjects age 15 years or over (response fraction of 81.6%). Results: 68.9% (95% confidence interval (CI) 66.2% to 71.7%) supported a totally smoke-free policy in restaurants. Experiences of discomfort or symptoms from second hand smoke in restaurants were common. The majority (77.2%, 95% CI 74.7% to 79.7%) anticipated no change in their frequency of use of restaurants after a smoke-free policy. Increased use was predicted by 19.7% (95% CI 17.3% to 22.1%) of respondents, whereas 3.2% (95% CI 2.2% to 4.4%) stated that they would dine out less often. In multivariate analyses, non-smokers (adjusted odds ratio (OR) 4.9), people who ate three times or less per week in restaurants as compared to those who ate >10 times per week (OR 2.1), those who had previous experience of discomfort from exposure to passive smoking in restaurants (OR 2.8), or who had avoided restaurants in the past because of smoking (OR 1.9), were more likely to support a totally smoke-free policy in restaurants. Smoke-free policies do not appear to have an adverse effect on restaurants, and may increase business by a considerable margin. Conclusion: This comprehensive survey—the first in Asia—shows strong community support for smoke-free dining and predicts an overall increase in the patronage of restaurants after the introduction of legislation for totally smoke-free restaurants.